2001
DOI: 10.1034/j.1399-6576.2001.045005612.x
|View full text |Cite
|
Sign up to set email alerts
|

Onset and duration of action of rocuronium – from tracheal intubation, through intense block to complete recovery

Abstract: The PTC method can be used to predict the time to first response to TOF nerve stimulation during intense rocuronium induced neuromuscular blockade. The relation between PTC and the time to T1 was prolonged after 1.2 mg/kg compared with 0.6 mg/kg and 0.9 mg/kg. No further improvement in intubation conditions at 60 s was evident by increasing the rocuronium dose from 0.9 mg/kg to 1.2 mg/kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 16 publications
(35 reference statements)
5
40
0
Order By: Relevance
“…the hypothesis that lidocaine could potentiate the neuromuscular blockade of rocuronium, decreasing its latency, was not demonstrated in the present study. the results were able to demonstrate statistical significance of the comparison among the latencies of two different doses of rocuronium, 0.6 mg.kg -1 and 1.2 mg.kg -1 , which has been widely divulgated in the literature 29,44 . Using the dose of 1.2 mg.kg -1 , indicated for rapid-sequence intubation, the latencies obtained were 47.40 seconds in the group that did not receive lidocaine, and 48.60 seconds in the group that received lidocaine, i.e., nearly ident ical.…”
Section: Discussionmentioning
confidence: 71%
“…the hypothesis that lidocaine could potentiate the neuromuscular blockade of rocuronium, decreasing its latency, was not demonstrated in the present study. the results were able to demonstrate statistical significance of the comparison among the latencies of two different doses of rocuronium, 0.6 mg.kg -1 and 1.2 mg.kg -1 , which has been widely divulgated in the literature 29,44 . Using the dose of 1.2 mg.kg -1 , indicated for rapid-sequence intubation, the latencies obtained were 47.40 seconds in the group that did not receive lidocaine, and 48.60 seconds in the group that received lidocaine, i.e., nearly ident ical.…”
Section: Discussionmentioning
confidence: 71%
“…PTC = post-tetanic count; R/L = right/left; T1 = first twitch height; TOF = train-of-four; T4/T1 = train-of-four ratio minutes, which is close to the recommended interval (six minutes) used in previous studies. [1][2][3][4][5][6] The PTC comprises a tetanic stimulation at 50 Hz for five seconds (250 impulses), followed by a three-second pause and then a series of 15 test stimuli at 1 Hz . Thus, the duration of this stimulation pattern is 23 sec with a total of 265 impulses.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have been performed with a six-minute delay between successive PTC stimulation without any firm evidence for the value. [1][2][3][4][5][6] Using the contralateral arm as control, Motamed et al found that repeating PTC every three minutes did not affect the time course of recovery during atracurium blockade. 8 Their findings contrast with those of Feldman et al who reported that, when an extremity is subjected to repeated tetanic stimulation, neuromuscular function remains enhanced when compared with the contralateral (control) arm.…”
Section: Résumémentioning
confidence: 99%
See 2 more Smart Citations